The Influence of Discount Cuts and Buzz Marketing Strategies on Live Sales Through E-commerce on Impulsive Buying Behavior - Ardiansyah Rasyid; Arifin Djakasaputra (Sultan Publisher, 2024)
The level of internet usage in Indonesia is considered very high, encouraging the community to continuously adapt to using technology as a medium for business creation. The utilization of technology in the business field requires business actors to enhance creativity and strategies to influence and attract consumer purchasing interest. This research will explain the influence of discounts and buzz marketing strategies on live sales through e-commerce on impulsive buying behavior, with respondents aged 15-29 who reside in Jakarta. The technique used in the research for sample selection is non-probability sampling with purposive sampling. Data collection in this research was conducted by distributing questionnaires. The research analysis technique used is Smart PLS. Ultimately, the results of this study show that discounts on live sales through e-commerce have a positive but insignificant effect on impulsive buying behavior. Meanwhile, buzz marketing in live sales through e-commerce has a significant positive effect on impulsive buying behavior.